Investigation of the effects of fused deposition modeling process parameters on the dimensional accuracy of PLA+ using the Taguchi method - Pristiansyah Pristiansyah; Muhammad Yunus; Andi Meri; Soni Afriansyah (Jurnal Polimesin, 2025)
Dimensional accuracy is a crucial aspect of 3D printing technology based on Fused Deposition Modeling (FDM), as deviations from the intended dimensions may lead to product malfunction and difficulties in component assembly. Such inaccuracies are generally influenced by various process parameters during 3D printing. This study aims to evaluate the effects of four main FDM parameters layer height, infill density, print speed, and nozzle temperature on the dimensional accuracy of printed parts using PLA+ material. The primary focus of this research is to enhance dimensional accuracy. To achieve this objective, the Taguchi design of experiments method was employed, offering a structured and efficient approach to optimizing process parameter settings while minimizing the required number of experiments. An L27 orthogonal array matrix was selected to analyze the influence of parameters at three levels. Based on the analysis of signal-to-noise (S/N) ratios and response data, the optimal parameter combination was identified as follows: layer height of 0.1 mm, infill density of 100%, print speed of 40 mm/s, and nozzle temperature of 210Â°C. Confirmation tests with these settings demonstrated a significant improvement in dimensional accuracy, with average measurements of 11.73 mm on the X-axis, 7.08 mm on the Y-axis, and 21.08 mm on the Z-axis. These results confirm that the selected parameter configuration is capable of ensuring dimensional stability and consistency.